AB0958 LOW-ENERGY PULSED ELECTROMAGNETIC FIELD THERAPY REDUCES PAIN IN FIBROMYALGIA: A RANDOMIZED SINGLE-BLIND CONTROLLED PILOT STUDY. (2nd June 2020) - Giovale, M.; Novelli, L.; Rampoldi, S.; Galli, R.; Monteforte, P.; Doveri, M.; Bianchi, G.; Bottaro, L. C.; Selmi, C.
Abstract : Background: Fibromyalgia is a clinical condition characterized by diffuse chronic muscle-skeletal pain, fatigue, sleep/mood disorders and muscular stiffness. The pathogenesis of fibromyalgia remains poorly understood but numerous lines of evidence suggest a role for alterations of both the central and peripheral nervous systems leading to heightened pain sensitivity along with a corollarium of other symptoms 1 . Low-energy pulsed electromagnetic field (PEMF) has promising data in the prevention of falls in senior individuals and is believed to promote osteogenesis and angiogenesis thus proving promising to treat bone diseases with chronic pain 2 . No data is available in fibromyalgia. Objectives: To investigate the efficacy and safety of PEMF on fibromyalgia symptoms in a randomized single-blind pilot study. Methods: We enrolled 21 women (median age 59 years, IQR 16, 5) affected by fibromyalgia according to the 2010 ACR classification criteria 3 not receiving chronic medical treatment for pain; patients were randomly allocated to receive PEMF TEPT (triple energy pain treatment) / New Sunrise 280 (THS - Therapeutic Solutions, Milan, Italy) on the selected points (10 agopuncture points) or scrambled points for 20 minutes at baseline (T0) and after 4 (T4) and 8 (T8) weeks. Outcome measures were recorded at T0, T4 and T8 and included FIQ (fibromyalgia impact questionnaire), WIP (widespread pain index), VAS pain, SS (symptom severity scale), and SF-36 (short form 36 health survey questionnaire). Results: Patients receiving the active treatment had a deep reduction of WIP from T0 to T8 (-76% vs -13% in placebo) with a statistically significant difference compared to the placebo group (p=0.0025) (Figure 1 ). In all endpoints, we observed a general reduction at T4 and T8 compared to T0 also for FIQ, VAS pain, SS, SF-36, regardless of the treatment arm and the decrease was higher in the active treatment arm compared to the placebo group, albeit not reaching statistical significance (Figure 2 ). Conclusion: The results of our pilot study show that PEMF is more effective than placebo in reducing widespread pain in fibromyalgia while confirming that a placebo effect is clear in this complex disease. References: [1]Targeting network hubs with noninvasive brain stimulation in patients with fibromyalgia Chelsea M. Kaplan, R.E. Harris, UnCheol Lee, Alexander F. DaSilva, George A. Mashour, Steven E. Harte. PAIN: January 2020 - Volume 161 - Issue 1 - p 43-46 [2]Yuan J, Xin F, Jiang W. Underlying Signaling Pathways and Therapeutic Applications of Pulsed Electromagnetic Fields in Bone Repair.Cell Physiol Biochem. 2018;46(4):1581-1594 [3]Wolfe F, Clauw DJ, Fitzcharles MA, et al. The American College of Rheumatology preliminary diagnostic criteria for fibromyalgia and measurement of symptom severity . Arthritis Care Res (Hoboken). 2010;62:600-61 Disclosure of Interests: Massimo Giovale: None declared, Lucia Novelli: None declared, Stefano Rampoldi: None declared, Rossana Galli: None declared, Patrizia Monteforte: None declared, Marica Doveri: None declared, Gerolamo Bianchi Grant/research support from: Celgene, Consultant of: Amgen, Janssen, Merck Sharp & Dohme, Novartis, UCB, Speakers bureau: Abbvie, Abiogen, Alfa-Sigma, Amgen, BMS, Celgene, Chiesi, Eli Lilly, GSK, Janssen, Medac, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Sanofi Genzyme, Servier, UCB, Luigi Carlo Bottaro: None declared, Carlo Selmi Grant/research support from: AbbVie, Janssen, MSD, Novartis, Pfizer, Celgene, and Leo Pharma, Consultant of: Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, Roche, and Sanofi-Regeneron, Speakers bureau: AbbVie, Aesku, Alfa-Wassermann, Bristol-Myers Squibb, Biogen, Celgene, Eli-Lilly, Grifols, Janssen, MSD, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB Pharma